Wage losses due to overqualification: the role of formal degrees and occupational skills - Kracke, Nancy; Reichelt, Malte; Vicari, Basha (Nürnberg, 2017)
"Wage penalties in overqualified employment are well documented, but little is known regarding the underlying mechanisms. We test two explanations, namely, formal overqualification and a mismatch of occupational skills. By using the National Educational Panel Study (NEPS) survey that is linked to German administrative data, we can objectively measure both types of mismatches. By using fixed-effects models, we confirm that overqualification is associated with a wage loss of approximately 5 percent, which indicates penalties from a lower requirement level. We find that some of this wage loss can be explained by a mismatch of skills between the current and training occupation. Further analyses show that mismatches of occupational skills explain the wage loss of the formal overqualification of employees with vocational training. For academics, both types of mismatch are unrelated. We conclude that because of occupational boundaries and more specific occupational skills, the people who are overqualified with vocational training more often work in jobs with lower and different skill requirements."